On the dynamics and control of a class of continuous digesters. (October 2015) - Schaum, Alexander; Alvarez, Jesus; Garcia-Sandoval, Juan P.; Gonzalez-Alvarez, Victor M.
Abstract : Highlights: The saturated OF control problem for a class of four-state anaerobic digesters with volatile fatty acids (VFA) measurement is addressed. The reactor must operate about a maximum VFA consumption steadystate that is locally stable and can be structurally unstable. The problem is addressed as an interlaced control-observer design in the light of passivity, observability, and bifurcation properties. A nonlocally robustly stabilizing saturated linear PI controller with antiwindup protection and tuning guidelines is obtained. Closed-loop robust stability conditions and comparison against optimality-based switching control are provided. Abstract: The saturated OF control problem for a class of four-state anaerobic digesters with volatile fatty acids (VFAs) measurement is addressed. The reactor must operate about an optimal steady-state, with maximum VFA consumption that is locally open-loop stable but not necessarily structurally stable. The problem is addressed as an interlaced control-observer design in the light of passivity, observability, and bifurcation properties. The result is a saturated linear PI controller with: (i) systematic construction and tuning and (ii) nonlocal robust stability conditions in terms of control gains and limits. The proposed approach is illustrated with a representative case example through numerical simulations, including a comparison with the switching control approach.